N-Doped carbon decorated with molybdenum disulfide with excellent electrochemical performance for lithium-ion batteries. Issue 79 (9th August 2016) - Liu, Jinbao; Liu, Yilin; Ai, Yani; Chen, Hongyan; Feng, Chenqi; Yu, Ningbo; Fu, Ning; Han, Sheng; Lin, Hualin
Abstract : Two-dimensional MoS2 nanoplates within N-doped carbon from polyaniline (PANI) were fabricated by a simple hydrothermal method. Abstract : Two-dimensional MoS2 nanoplates within N-doped carbon from polyaniline (PANI) were fabricated by a simple hydrothermal method. During this process, PANI facilitated the absorption of inorganic precursors and provided confined spaces for the growth of MoS3 nanoparticles in the case of the unwanted aggregations. The unique nanostructure and composition of the nanoplates achieved high capacity. When CNFs@NC/MoS2 was used as an anode in lithium-ion batteries, it maintained an ultrahigh capacity of 900.9 mA h g −1 at a current density of 200 mA g −1 for 80 cycles. Even when the current density returned to 100 mA g −1 after cycling at different rates, a capacity of 998 mA h g −1 was still achieved.